2020 : renewing the paradigms for orofacial pain = 2020 : renovando los paradigmas para el dolor orofacial - Chavarría Bolaños, Daniel 1982-
In 2020, two important changes were adapted by the international health community: a new definition of pain and a new classification for orofacial pain conditions. With these changes new tasks and challenges also emerged, and clinicians from several disciplines begun to adopt and reconsidered classic paradigms, and the policies derived from them. This new perspective article, examine the new definition of pain proposed by the International Association for the Study of Pain, and the new International Classification of Orofacial Pain; analyzing the positive impact and further perspectives of these.